Digital technology in physical education distance learning during pandemic: teachers’ perspective - Soni Nopembri; Saryono Saryono; Nur Rohmah Muktiani; Anastasia Erlina Listyarinni; Mohd Izwan bin Shahril (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
The aims of study to describe the utilization of information technology and telecommunications in Physical Education (PE) distance learning process during the covid-19 pandemic. This quantitative study conducted with a survey method. The subjects of this study were primary and secondary school PE teachers who were determined based on clusters of three regions/regions, namely: schools in urban, suburban, and rural areas in the Special Region of Yogyakarta with a total of 238 people. Data was collected through a questionnaire distributed to the primary and secondary school PE teachers online and offline. The data analysis applied is descriptive quantitative with percentages. The results of the study show that PE teachers apply hardware and software that already exist and are popular in Indonesia. PE teachers communicate with their students, especially WhatsApp, Email, Instagram, and Facebook, and also use social media applications in various ways. The utilzation of the Google Classroom as a Learning Management System (LMS) is very dominant.